P3.96 Factors associated with commercial sexual behaviour among men who have sex with men in shenzhen, 2011 to 2015. (8th July 2017) - Fuchang, Hong; Yumao, Cai; Yonghui, Lai; Lizhang, Wen; Weiye, Yu; Hui, Liu
Abstract : Introduction: With the use of new-type drugs, Money boys(MB) will have unprotected sex and injection behaviours easily, thus accelerate the spread of HIV among men who have sex with men(MSM) through sexual transmission and blood transmission. Our study is to investigate the status and factors associated with commercial sexual behaviour among MSM in Shenzhen, China. Methods: Convenience sampling method was used to recruit MSM from 2011 to 2015. Questionnaire-based interviews were conducted on a one-on-one basis. Data were collected including socio-demographic information, HIV testing history, history of blood donation and drug abuse in recent two years, self-identified sexual orientation, role in homosexual behaviour, ever being MB and clients of MB. 5 ml blood samples were taken and tested for treponema pallidum and HIV antibodies. Results: Among the total of 3040 MSM recruited, 341 (11.2%) reported ever being MB. The prevalence of syphilis, HIV, and syphilis-HIV co-infection among MB were 27.0%, 16.4%, and 8.8% and those among general MSM were 17.2%, 8.9% and 4.6%, respectively. Compared with general MSM, MB had significantly higher prevalence of syphilis, HIV, and syphilis-HIV co-infection. In the multivariate logistic regression analysis, MSM aged greater than 30 years, having college or above education level, residing in Shenzhen for 0.5~3.0 years and greater than 3.0 years were less likely to serve as MB in comparison with those aged less than 30 years, having high school or below education level, residing in Shenzhen for less than 0.5 years. Monthly income more than 5000 Yuan, having drug abuse history, ever being clients of MB, ever reported both insertive and receptive anal sex behaviours will increase the risk of serving as MB among MSM in comparison with monthly income less than 3000 Yuan, never having drug abuse, never being clients of MB and ever reported predominantly insertive anal sex behaviours. Conclusion: Various factors were associated with MSM serving as MB and needed to be considered when designing syphilis/HIV prevention programs targeted them.